Successful management of gingival recession with interdental attachment loss using gingival unit grafts - Neelima Katti; Devapratim Mohanty; Poonam Agrawal; Subash Chandra Raj; Shib Shankar Pradhan; Debjani Baral (Wolters Kluwer Medknow Publications, 2022)
Background: Gingival recession leads to root surface exposure devoid of periodontal attachment. Recession defects with interdental attachment loss (RT2, RT3), further increase the avascular area which is critical for survival of soft-tissue grafts. Nonsubmerged grafts such as free gingival grafts and gingival unit grafts (GUGs) rely primarily on plasmatic circulation from the recipient area during the initial stages of healing for its survival. Methods: Nineteen isolated RT2 recession defects, in the mandibular anterior region, were treated using GUG. The clinical parameters of recession depth (RD), recession width (RW), interdental clinical attachment levels (iCAL) were measured at baseline. Percentage of mean root coverage (MRC) was calculated at 3 months and 6 months. Results: The percentage of mean root coverage (MRC) achieved at the end of 6 months was 81.79% ± 6.16%. Further, Simple linear regression analysis to predict MRC at 6 months using baseline RW revealed, for every 1 mm decrease in RW, the percentage of root coverage significantly increased by 5.25% (P = 0.04). Conclusion: GUG can be used as an alternative treatment modality to achieve successful root coverage in RT2 recession defects. Baseline RW can be used to predict the outcome of root coverage at the end of 6 months.